Techniques of Historical Narrative in "Me Suzam": Criticism and Analysis - Bibi, Naeema; Yaqoob, Ghazal (sourcecoder, 2023)
Historiographic Metafiction is a term coined by Linda Hutcheon (Canadian literary theorist). Presented around 1980. The term is used for fictional texts that combine metafiction with historical narrative. Such texts also contain many historical and literary references. Me Suzam is Humira Ashfaq’s first novel. It can rightly be called a historical novel, A lot of historical events are present in this novel, This novel is the story of the poet who first became known as Rabia Balkhi and later Rabia Khuzdari. Born a thousand years ago, Rabia was a Persian and Arabic poetess and the daughter of Baluchistan, who was the first victim of entrepreneurship. Rabia was a contemporary of the famous Persian poet Raduki, who belonged to the beautiful region of Balochistan, Khuzdar. Apart from being a poet who was fond of poetry, Rabia was also a painter, she is counted among the historical women who named their era with their own name with their intelligence. Humira Ashfaq has presented the life of this unfortunate princess in this novel, who had to become a victim of the tribal customs and traditions of Balochistan and also faced many difficulties. In this paper, this novel has been analyzed in the context of historical narrative.